Metodologias ativas: potencialidades e limitações na percepção de professores da educação básica - Ferreira, Sergio Daniel (2021)
Active learning methodologies have gained increasing visibility in discussions about education with regard to increasing student engagement, whether from the perspective of working from problem situations or by projects. Linked to these methodologies, many nomenclatures such as PBL (Problem Based Learning), Active and Student-Centered Learning, Case-Based Learning, Maker Movement and other derivations, have appeared as potential solutions for teaching practices in schools in the sense of connecting curriculum and to foster interdisciplinarity, student protagonism and learning through group work. Considering that the protagonism or engagement of young people in the school environment provides an amalgamation that connects them to teachers and the school, and at the same time it can provide greater autonomy from problem situations that require these young people to critically analyze and take action. decision, it is glimpsed that such methodologies can help in the construction of educational practices that are seductive to the eyes of students, without giving up systematized knowledge. From this perspective, the potential and limitations of active methodologies are discussed in the view of a group of basic education teachers – Elementary Education II, from schools accredited to the Integral Education Program (PEI) of the State of São Paulo, having as cut out the electives. With these questions, we anchored our research in schools belonging to PEI through a social project called Tetear Tech, aimed at creating a space for dialogue and learning involving art and technology as a way to expand the repertoire of students. The social project connected four schools in Piracicaba-SP, offering training workshops embedded in active methodologies. In addition to this pedagogical intervention process, there was the elaboration of a Thesaurus of its own, with the choice of keywords for the search for academic papers on active methodologies, in order to try to understand the academic production on this topic in the field of education in Brazil. For this survey, we used the theses bank of graduate programs in education with grades of 5-7 from the Coordination for the Improvement of Higher Education Personnel (Capes), mapped by Grupo Horizonte (Study and Research Group of UFSCar), and the works published on the SciELO platform. The material collected, organized, and presented in this research showed an increase in the number of works produced on active methodologies, mainly directed to higher education in the area of health and graduation in medicine and nursing; however, there is no significant academic production focused on basic education. In the intervention research carried out, the teachers involved in the process were optimistic and inclined to incorporate new methods and/or approaches involving practices related to active methodologies in their classroom planning and practices. However, these professionals have little contact with activities linked to active methodologies and space for continuing education for discussion and sharing of good practices.